2022
DOI: 10.1002/macp.202200154
|View full text |Cite
|
Sign up to set email alerts
|

Printed Polymer‐Stabilized Chiral Nematic Liquid Crystal Privacy Windows

Abstract: In this paper, drop-on-demand (DoD) printing is demonstrated of polymer stabilized chiral nematic liquid crystal (PSCLC) privacy windows that can function in either a conventional mode (scattering to transparent) or reverse mode (transparent to scattering) with the application of an electric field. Inkjet printed droplets of the PSCLC mixture, with diameters of the order of 100-200 μm and sandwiched in LC layer thicknesses of ≈10-15 μm, are characterized in terms of their transmission as a function of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The scattering based technologies include polymer dispersed liquid crystals (PDLCs), [16][17][18][19][20][21] polymer stabilized liquid crystal (PSLC), [22][23][24][25][26][27][28][29] and polymerstabilized cholesteric textures (PSCTs). [30][31][32][33][34][35][36][37] In one state under a specific voltage condition, the liquid crystal in the window is in an optically uniform state and is transparent. In another state with a different voltage condition, the liquid crystal is in a multidomain state and is scattering.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering based technologies include polymer dispersed liquid crystals (PDLCs), [16][17][18][19][20][21] polymer stabilized liquid crystal (PSLC), [22][23][24][25][26][27][28][29] and polymerstabilized cholesteric textures (PSCTs). [30][31][32][33][34][35][36][37] In one state under a specific voltage condition, the liquid crystal in the window is in an optically uniform state and is transparent. In another state with a different voltage condition, the liquid crystal is in a multidomain state and is scattering.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Our group have also recently used inkjet printing to fabricate polymer-dispersed LC smart/privacy windows with embedded logos and images. [30,31] Very recently, Coppola et al have DOI: 10.1002/adem.202400245 Electrohydrodynamic (EHD) printing of nematic liquid crystals (LCs) is demonstrated. Miniscule LC droplets, as small as 1 micron, are generated with the EHD printing system and deposited with high precision onto a glass substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] Our group have also recently used inkjet printing to fabricate polymer‐dispersed LC smart/privacy windows with embedded logos and images. [ 30,31 ] Very recently, Coppola et al have reported the deposition of nematic LC droplets for microlens applications with sizes around 400 μm using a pyro‐electrohydrodynamic technique. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%